Electronic leadership – Proposed Practical Model – - al-Shihri, Ajlan bin Mohammed (Journal of Economic, Administrative and Legal Sciences, 2018)
Organizations, especially government agencies, have witnessed large shifts in the technological field, as a result of what information communications technologies have produced. That is why it has become very important, that there should be a leadership that keep up with these technological transformations. Methods and attributes of leadership are no longer suitable as they were during last decades. From this point of view, this study deals with electronic leadership in terms of the concept, importance and challenges designed to influence the behavior of individuals, the accomplishment of business, and to achieve the goals of these organizations to keep pace with these technological developments. Since this electronic leadership was produced through what the successive technological revolutions have created especially information communications technologies, the study aimed to review the importance of these technologies and its challenges, as well as the characteristics and features of electronic organizational entities electronic. The study also dealt with e- leaders, their responsibilities, and their potential and anticipated roles in such electronic entities . Due to the acceleration of the technological revolution, which no doubt will prosper, spread out and will be an urgent requirement in the modern era organizations and shift of organizational structures in response to these changes. The study concluded with presenting the proposed practical model to adopt the e-leadership in organizations. This model includes six phases represented in complete knowledge of the dimensions of the electronic leadership, its consequences and its near future. The second phase is the need to measure the technical readiness on the level of organization and the leaders. The third phase is the importance of the availability of modern organizational entities. The fourth phase is building human capacities able to practice electronic leadership. The fifth phase is the adoption process. The sixth and the last phase is to assess and develop this adoption process. The study concluded with a brief summary about what has been deduced from the presentation of study subjects, and the recommendations directed to interested researchers, practitioners and agencies to adopt electronic leadership.